You need to use mathematical induction to prove the formula for every positive integer n, hence, you need to perform the two steps of the method, such that:
Step 1: Basis: Show that the statement P(n) hold for n = 1, such that:
`(1 + 1/1) = 1+1 => 2=2`
Step 2: Inductive step: Show that if P(k) holds, then also P(k + 1) holds:
`P(k): (1 + 1/1)(1 + 1/2)...(1+1/k) = k + 1` holds
`P(k+1): (1 + 1/1)(1 + 1/2)...(1+1/k)(1 + 1/(k+1)) = k+2`
You need to use induction hypothesis that P(k) holds, hence, you need to re-write the left side, such that:
` (k + 1)(1 + 1/(k+1)) = k + 2`
Multiply k+1 to the left side:
`k+1 + (k+1)/(k+1) = k+2`
`k + 1 + 1 = k + 2`
`k + 2 = k + 2`
Notice that P(k+1) holds.
Hence, since both the basis and the inductive step have been verified, by mathematical induction, the statement `P(n):(1 + 1/1)(1 + 1/2)...(1+1/n) =n + 1` holds for all positive integers n.
No comments:
Post a Comment